STRATEGI PEMERINTAH DAERAH DALAM MENGATASI KEMISKINAN DI KABUPATEN SIDENRENG RAPPANG (STUDI PADA KECAMATAN KULO): - Jamal; Ahmad Mustanir (LPPM Universitas Abdurrab, 2026)
Poverty remains one of the fundamental challenges faced by local governments, including Sidenreng Rappang Regency. This study aims to analyze local government strategies in addressing poverty through social assistance programs, community empowerment initiatives, as well as the role of local institutions and implementation barriers. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Data analysis was conducted thematically with the support of NVivo software to identify patterns, themes, and relationships among actors involved in poverty alleviation efforts.The findings indicate that local government strategies comprise two main approaches. First, short-term strategies involve the distribution of social assistance such as Non-Cash Food Assistance (BPNT), the Family Hope Program (PKH), food aid, and other emergency interventions to reduce the burden on poor households. Second, long-term strategies focus on community empowerment through skills training, strengthening the agricultural and micro, small, and medium enterprise (MSME) sectors, mentoring of business groups, and enhancing productive economic capacity. The Social Affairs Office acts as the coordinating body for program implementation, while village governments serve as strategic partners in data collection, facilitation, and ensuring community participation.This study also identifies several obstacles, including inaccuracies in beneficiary data, low community motivation to participate in empowerment programs, limited budget availability, and weak cross-sectoral coordination. These findings underscore the need to strengthen data governance, increase community participation, and conduct continuous evaluation to ensure the effectiveness of poverty alleviation strategies.